An analysis of micro deep drawing of ferritic stainless steel 430 using crystal plasticity finite element method - Jingwei Zhao; Zhengyi Jiang; Zhihua Wang; Shengbo Sang; Leszek A. Dobrzański; Ming Yang; Xiaoguang Ma; Yongzhen Wang (Journal of Materials Research and Technology, 2022)
In this study, a numerical simulation model based on crystal plasticity theories was established in order to study the micro deep drawing (MDD) process of ferritic stainless steel (FSS) 430 foils (50 μm thickness). The numerical simulation results obtained using the crystal plasticity finite element method (CPFEM) match well with experimental values, which indicates that the CPFEM can be utilized to analyze the forming performance of FSS foils during MDD. The results show that optimal annealing temperatures are 850 and 900 °C, which benefits both the surface quality of drawn cups and the formability of FSS 430 foils. During MDD process, remarkable thinning occurs at the nose radius area while the maximum thickness is found at the cup mouth area due to metal flow. The thickness is reduced by about 10% at the nose radius area and increased by about 20% at the cup mouth area. It is also found that the surface quality of drawn cups can be improved by applying appropriate blank holding force during MDD process.